2018
DOI: 10.4236/ijoc.2018.81003
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Various Oxides and Mesoporous Materials Containing Niobium and Sulfate Ions, in the Oxidation Reaction of 1-Octanol

Abstract: Several types of solid acid catalysts were prepared based on oxides like (ZrO 2 , TiO 2 , HfO 2 , MCM-41 and SBA-15). Each catalyst was subjected separately to two types of impregnations: sulfate ions and niobium. The catalytic activity of these solids was tested in the oxidation reaction of 1-octanol. These catalysts showed acidic and redox characters. MCM-41 and SBA-15 materials showed higher redox catalytic activities through the formation of (octyl octanoate, peroxyacetal and octanal). Our interest was foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Several research groups have investigated the oxidation of primary alcohols with the aid of catalysts for synthesis purposes (to increase yield and product selectivity). [28][29][30][31][32][33][34][35][36] For example, Ishida et al, 30 Kotolevich et al, 32 Jenzer et al 34 and Iwahama et al 35 oxidized 1-octanol using various catalysts and found several aging products (aldehydes, acids, esters). Hussein et al 31 also found an ether and a peroxy-acetal as aging products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have investigated the oxidation of primary alcohols with the aid of catalysts for synthesis purposes (to increase yield and product selectivity). [28][29][30][31][32][33][34][35][36] For example, Ishida et al, 30 Kotolevich et al, 32 Jenzer et al 34 and Iwahama et al 35 oxidized 1-octanol using various catalysts and found several aging products (aldehydes, acids, esters). Hussein et al 31 also found an ether and a peroxy-acetal as aging products.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36] For example, Ishida et al, 30 Kotolevich et al, 32 Jenzer et al 34 and Iwahama et al 35 oxidized 1-octanol using various catalysts and found several aging products (aldehydes, acids, esters). Hussein et al 31 also found an ether and a peroxy-acetal as aging products. Guillard et al 36 oxidized 1-octanol with ultrasound and photocatalysis and detected several aldehydes, alkanes and alkenes as aging products.…”
Section: Introductionmentioning
confidence: 99%